Russian Federation : 2018 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Russia's economy is recovering from the 2015-2016 recession, thanks to the authorities' effective policy response and higher oil prices. Output increased by 1.5 percent in 2017 on the back of robust domestic demand, but short of expectations. Growth is projected at 1.7 percent in 2018, supported by rising credit and disposable incomes. Headline inflation is projected to bounce back during the second half of 2018 to 3.5 percent at year end, supported by the ongoing domestic demand recovery, pass-through from the recent ruble depreciation, and the fading of temporary factors. The medium-term outlook remains muted, owing to structural bottlenecks and the lingering impact of sanctions.